Metaphorical Expressions of Karakalpak Culture in Traditional Folk Songs - Makhsetdullaevna, Kamalova Gulmaryam; Minajatdinovna, Tazhetdinova Sofia; Muratbayevich, Saparov Rakhim; Jabbarbergenovich, Allanov Ayapbergen; Kadyrbaevna, Urazbaeva Gulshirin; Romanovna, Orazalieva Raziya (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
This study examines the role of metaphors in Karakalpak folk songs, with a specific focus on three traditional songs: Aqsúńgil, Yasha páriy, and Qız Minayım. Using a qualitative ethnolinguistic approach, the research explores how metaphors in these folk songs reflect and reinforce key cultural values, social structures, and norms within Karakalpak society. Metaphors are recognized as essential tools for conveying cultural beliefs about leadership, community responsibility, gender roles, and romantic relationships. The analysis categorizes metaphors based on Lakoff and Johnson’s typology, distinguishing between ontological, structural, and container metaphors. The findings highlight how metaphors like “settling the lands”, “driving herds of livestock”, and “choosing the finest youths” underscore the cultural importance of land, livelihood, and women’s roles as leaders and nurturers. Similarly, metaphors such as “multicolored dress” and “dawn breaking” reflect the deep connection between nature, beauty, and romantic love. These figurative expressions not only enrich the poetic quality of the songs but also embody fundamental aspects of Karakalpak worldview, where emotional connections and social unity are intertwined with the natural world’s rhythms. By examining the metaphors in these folk songs, this paper contributes to the ethnolinguistic understanding of how language and culture are intertwined, offering new insights into the cultural identity of the Karakalpak people. The study highlights the importance of metaphor in shaping social relationships, fostering community cohesion, and transmitting cultural knowledge across generations. The research also opens avenues for future studies on the role of metaphor in other forms of oral literature in Central Asia.